1999
DOI: 10.1007/s002510050569
|View full text |Cite
|
Sign up to set email alerts
|

Allelic diversity at the Mhc-DQA locus in cotton rats ( Sigmodon hispidus ) and a comparison of DQA sequences within the family Muridae (Mammalia: Rodentia)

Abstract: The cotton rat (Sigmodon hispidus) is a common murid rodent of the southern United States, Mexico, and Central America. Using single-stranded conformation polymorphism analysis and DNA sequencing techniques, 11 DQA exon 2 alleles were detected among 180 S. hispidus from Caddo County, Oklahoma, USA. The alleles represent a single locus exhibiting a high level of polymorphism. Nucleotide and amino acid distance values among DQA alleles of S. hispidus were higher than those within Mus musculus and species of Ratt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
2
26
0
1
Order By: Relevance
“…Although Garrigan and Hedrick 8 did not find a statistically significant difference in the w ratio inside and outside the HLA-DQB PBR, Hughes and Yeager, 1 reached the opposite conclusion by finding that d N greatly exceeded d S within the PBR. Similarly, Pfau et al 9 and De Bellocq et al 10 did not find evidence of positive selection in the cotton rat (Sigmodon hispidus) and the European woodmouse (Apodemus sylvaticus) DQA genes, respectively. In contrast, Bryja et al 11 identified a clear signature of positive selection in closely related rodent species.…”
Section: 2mentioning
confidence: 99%
“…Although Garrigan and Hedrick 8 did not find a statistically significant difference in the w ratio inside and outside the HLA-DQB PBR, Hughes and Yeager, 1 reached the opposite conclusion by finding that d N greatly exceeded d S within the PBR. Similarly, Pfau et al 9 and De Bellocq et al 10 did not find evidence of positive selection in the cotton rat (Sigmodon hispidus) and the European woodmouse (Apodemus sylvaticus) DQA genes, respectively. In contrast, Bryja et al 11 identified a clear signature of positive selection in closely related rodent species.…”
Section: 2mentioning
confidence: 99%
“…Ross seals.-We analyzed 35 Ross seals, 1st by cloning and sequence analysis of MDQA1þMDQA2 PCR products, and Residue numbering scheme is based on cotton rat (Sigmodon hispidus- Pfau et al 1999). Dots indicate residues identical to the top sequence, allele W6 from Weddell seals.…”
Section: Resultsmentioning
confidence: 99%
“…However, the transspecies polymorphism detected across 16 rodent species in this study may result from greater similarities between alleles shared between ancestral duplicated loci compared to alleles from paralogous loci within the same species. It is interesting that evidence from the DRB gene supports the conservation of alleles across species, a pattern that diverges from the DQA (a different MHC II gene) which does not show clear evidence for transspecies polymorphism in rodents (Pfau et al 1999). Whether this difference in allelic preservation is due to biological function or architecture of the specific genes remains to be determined.…”
Section: Discussionmentioning
confidence: 99%